Dinamika Pencatatan Perkawinan di Indonesia - Hanapi, Agustin; Shoim, Shoim (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: Apart from being regulated through Islamic law, the rules regarding marriage are sourced from the Al-Qur'an and hadith, in the dynamics of the state in Indonesia, marriage is also regulated in laws and government regulations. In the Marriage Law Number 1 of 1974 as amended by Law Number 19 of the year, marriages are required to be registered, but in fact many people are reluctant to register these marriages, so many people call them sirri marriages, the meaning of sirri marriage is marriage. which is valid because it is carried out in accordance with the provisions of religious law, namely by fulfilling the pillars and conditions of marriage, but the marriage does not receive state recognition because it is not registered. Siri marriages cause many problems, especially legal problems in the family, such as the absence of legal recognition of the marriage and other problems that follow such as the status of children who do not get marriage certificates, other family rights, especially the rights of women (wives) and children who often does not receive recognition from his father and/or his father's family, such as receiving maintenance and inheritance rights from his father. Marriage registration is actually an effort to provide legal protection for families regarding the rights that must be obtained properly from a marriage, and marriage registration, although not prescribed in the Islamic religion, is actually not in conflict with Islamic law and is even recommended with the aim of avoiding harm and problems that arise. it may occur later in the family.Keywords: Family, Marriage, Siri, Islamic Law, Laws and Registration. Abstrak : Aturan mengenai perkawinan selain diatur melalui syariat Islam yaitu bersumber dari Al-Qur’an dan hadits, dalam dinamika bernegara di indonesia Perkawinan Juga diatur di dalam Undang-Undang dan Peraturan Pemerintah. Didalam Undang-undang perkawinan Nomor 1 tahun 1974 sebagaimana telah dirubah melalui Undang-undang Nomor 19 tahun bahwa Perkawinan wajib untuk dicatatkan, namun pada faktanya banyak masyarakat yang enggan mencatatkan perkawinan tersebut, sehingga banyak yang menyebutnya dengan istilah perkawinan sirri, pengertian perkawinan sirri adalah perkawinan yang sah karena dilaksanakan sesuai dengan ketentuan hukum agama, yaitu dengan terpenuhinya rukun dan syarat perkawinan, hanya saja perkawinan tersebut tidak mendapat pengakuan negara karena tidak tercatat. perkawinan siri banyak menimbulkan problem terutama problem hukum dalam keluarga, seperti tidak adanya pengakuan hukum terhadap perkawinan tersebut dan problem lain yang mengikutinya seperti status anak yang tidak mendapatkan akte nikah, hak-hak keluarga lainnya terutama hak-hak perempuan (istri) dan anak yang sering tidak mendapat pengakuan dari bapak dan atau keluarga bapaknya seperti untuk mendapat hak nafkah dan waris dari bapaknya. Pencatatan perkawinan sesungguhnya adalah upaya untuk memberikan perlindungan hukum bagi keluarga terhadap hak-hak yang harus didapatkan sebagaimana mestinya dari sebuah perkawinan, dan pencatatan perkawinan meski tidak disyariat dalam agama Islam tetapi sesungguhnya tidak bertentangan dengan hukum Islam dan bahkan dianjurkan dengan tujuan menghindari kemudaratan dan problem yang mungkin akan terjadi di kemudian hari dalam keluarga.Kata kunci : Keluarga, Kawin, Siri, Hukum Islam, Undang-Undang dan Pencatatan.